Oh my gad! A case study on the implementation of gender and development among private Higher Education Institutions (HEIS) - Gil JR., Tyrone O. (Penerbit Universiti Kebangsaan Malaysia, 2021)
The advancement towards gender equality had been made clear through the insertion of Gender and Development among the UNDP Goals. At the school level, certain measures had been implemented to answer the call for gender and development. This case study will examine the status of implementation of Gender and Development among private Higher Education Institutions (HEIs) in Tacloban City, Philippines, based on the mandated CHED Memorandum No. 1 s. 2015 on the Implementation of GAD among Higher Learning Institutions. With GAD focal persons as the primary participants, exhaustive data was gathered and analyzed. GAD programs, activities, and projects, program planning, implementation, and evaluation, problems encountered in the implementation, differing school policies were the emerging themes from the data. The study concluded that private HEIs must recognize a sustainable and meaningful GAD program, activities, and projects to be implemented in their respective schools.